Compelling Issues Compounding the Understanding of Low Dose Radiation Effects: But Do They Matter?. Issue 3 (March 2016) - Morgan, William F.
Abstract : Abstract: Recent advances in low dose radiation research have raised a number of compelling issues that have compounded the understanding of low dose radiation effects. Here some of them are outlined: the linear no-threshold model for predicting effects at low radiation doses, dose rate effectiveness factor, attributability, and public perception of low dose radiation effects. The impact of changes in any of these hotly debated issues on radiation protection is considered.